Organizational Communication of Village Heads in Providing Anti-Corruption Services to Support Sustainability Development Goals (SDGs) - Gartina, Roro Gina; Lestari, Martha Tri (Future Science, 2024)
Corruption is a big challenge in achieving the Sustainable Development Goals (SDGs). This research aims to determine the role of organizational communication carried out by the Head of Haurgeulis Village in providing anti-corruption services that support SDGs 16, which focuses on peace, justice and strong institutions. The research method is qualitative with a case study approach in Haurgeulis Village, West Java. The results show that effective communication by the Village Head is crucial in increasing transparency, community participation, information accessibility and responsiveness of public services. Transparency is achieved through periodic financial reports, open meetings, and publication of documents that can be accessed by village residents. Community participation is increased by active involvement in decision making through working groups and discussion forums. Accessibility of information increases through notice boards, social media and village apps, enabling residents to better understand their rights and obligations. The responsiveness of public services can be seen from the Village Head's ability to respond quickly to complaints and input. The study also found that information and communication technology, such as village applications, websites and social media, contributed greatly to communication. This technology accelerates the dissemination of information and responses to public input. Dialogue forums between the village government are effective in discussing important issues, formulating policies and solving common problems. In conclusion, Village Head communication is the key to strengthening transparent and accountable village governance and supporting sustainable development. Good communication creates an environment that supports peace, justice and strong institutions in line with SDG target 16.